Social and structural vulnerabilities: Associations with disaster readiness. (January 2023) - Rao, Smitha; Doherty, Fiona C.; Teixeira, Samantha; Takeuchi, David T.; Pandey, Shanta
Highlights: We extend scholarship on sociodemographic determinants of disaster preparedness. Housing security and quality were vital for disaster preparedness in the household. Presence of an older adult at home was associated with higher preparedness. Housing insecurity moderates social vulnerability's association with preparedness. Abstract: The ability to plan for a disaster is associated with a range of contextual factors and often traverses several sites of inequities, including sociodemographic and institutional disparities. While multiple studies have investigated the relationship of housing insecurity with adverse outcomes after a disaster, fewer studies have examined how housing insecurity is associated with disaster preparedness. This paper hypothesizes social and structural vulnerabilities to be directly associated with preparedness. Housing insecurity is posited to have both direct and multiplicative effects with social vulnerability on the dependent variable. We use nationally representative data from the 2017 American Housing Survey. The final weighted study sample consisted of 29, 070 housing units, with 52% male and 48% female householders. Fifty-seven percent of the population was not prepared with food, water, emergency funds, and transportation. Housing security and quality emerged as important conditions for households to be better prepared. Further, housing insecurity moderated the relationship between some social vulnerability factors and preparedness. The study helps identify where resources and research funds should be targeted to reduce multidimensional vulnerabilities before a disaster. Safe and affordable housing is central to climate and environmental justice; centering disaster readiness, response, and climate action across policy agendas is vital.